Relationship between Nurses’ Attitudes and Satisfaction with Bedside Shift Reports and Patient Safety Culture - Samara Jaber; Mirna Fawaz; Ahmad Rayan; Nisser Alhroub; Mohammad Suliman; Mohammed ALBashtawy; Rasmieh Al-Amer; Abdullah Alkhawaldeh (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: A thoroughly standardized nurse bedside shift report, including effective communication, may improve nurses’ satisfaction and patients’ safety. However, a few studies were found that measure the relationships between nurses’ attitudes and satisfaction with bedside shift reports and patient safety outcomes.Purpose: This study aimed to measure nurses’ attitudes and satisfaction with bedside shift reports and their relationships with patient safety culture.Methods: A cross-sectional and descriptive study was conducted between May to August 2021 among 90 bedside nurses conveniently recruited from a public hospital in Lebanon. The Bedside Handover Report Staff Nurses’ Satisfaction Survey and the Survey on Patient Safety (SOPS) were used to collect data. Data were analyzed using descriptive statistics such as mean and standard deviation and inferential statistics, i.e., Pearson correlation coefficient.Results: The results showed that satisfaction scores were high in all the questions in the bedside shift reporting. The participants showed relatively positive attitudes towards bedside shift reports where all the statements recorded above-average mean values. The highest-ranking statement “bedside shift report is completed in a reasonable time” was recorded with a mean value of 3.35 (SD=0.87), while the lowest-ranking statement was “bedside shift report is relatively stress-free” with a mean value of 2.03 (SD=0.86). There were significant relationships between nurses’ satisfaction with shift reports and some patient safety culture composites, such as between nurses’ satisfaction with bedside shift reports and communication about errors and reporting of patient safety events (p<0.05) and between nurses’ attitudes toward bedside shift reports and communication about errors (p<0.001)Conclusion: Implementation of the bedside shift report improves nurses’ levels of satisfaction, enhances positive attitudes toward work, and enhances patients' safety. Nursing leaders should encourage nurses to implement bedside handover reports in their hospitals.